The Influence of Digital Marketing, Word of Mouth, and Product Quality on Purchasing Decisions (A Study of Azarine Consumers in Medan City) - Lydia Natalia Samosir; Ainun Mardhiyah; Onan Marakali Siregar (Review of Human Resources, Organizational Change, and Economic Impact, 2025)
This study examines the effects of digital marketing, word-of-mouth communication, and product quality on consumer purchasing decisions for Azarine products. Using a quantitative approach, the research analyzed both individual and combined impacts of these factors on consumer buying behavior. A purposive sampling method recruited 100 Azarine product users in Medan City. Primary data was collected through questionnaires, while secondary data came from literature review. Data analysis used SPSS including validity tests, reliability assessments, classical assumption tests, multiple linear regression, and coefficient of determination analysis. Results show digital marketing significantly influences purchase decisions (t = 11.499 > 1.985, p < 0.05) with a positive regression coefficient of 0.164. Word-of-mouth demonstrates significant positive impact (t = 7.958 > 1.985, p < 0.05) with regression coefficient of 0.155. Product quality positively affects purchase decisions (t = 2.079 > 1.985, p = 0.011 < 0.05) with regression coefficient of 0.044. The three variables collectively explain 66.9% of variance in purchase decisions (Adjusted R² = 0.669), indicating substantial explanatory power. The remaining 33.1% is attributed to external factors not included in this model. These findings suggest companies should emphasize digital marketing strategies, encourage positive word-of-mouth, and maintain high product quality to enhance consumer purchasing intentions. The study provides valuable insights for marketing professionals seeking to maximize consumer behavior influence through integrated promotional approaches.